Effect of contrast agent dosage on longitudinal relaxation time, signal and apparent tumor volume in glioblastoma at 9.4T = Auswirkungen der Kontrastmitteldosis auf longitudinale Relaxationszeit, Signal und sichtbares Tumorvolumen in Glioblastomas bei 9,4 Tesla - Königsberg, Alina; Fischer, Manuel; Bendszus, Martin; Heiland, Sabine (Zeitschrift für medizinische Physik, 2019)
Introduction - Glioblastoma multiforme is the most frequent innate brain tumor and still yields an unfavorable prognosis of 15 months of survival after diagnosis. Animal models play an important role in the investigation of therapeutic strategies of brain tumors. Thereby, MRI is substantial to individual follow-up examination for therapeutic response. Contrast agent dosage at 1.5 and 3T MRI has been thoroughly tested, while there is hardly any data for 9.4T. Therefore, the aim of this study was to find the optimal contrast agent dosage at 9.4T for examination of T1 relaxation time and apparent tumor volume in an animal model. - Material and methods - Six animals with a U-87 glioblastoma were part of this study. Scans were performed on a 9.4T MRI. The MRI protocol contained a standard T1w sequence, which was employed for tumor volumetry and signal intensity measurement after single, double and triple contrast agent dosage injections and a T2w sequence for volumetry of tumor and edema. From a T1 map, T1 relaxation times and tumor area were measured. Histologic tumor size measurements were also performed for two animals. - Results - The mean apparent tumor volume in T1w MRI increased significantly with each additional contrast agent injection, mainly due to the increase of the hyperintense tumor rim. Volumetry based on T2w MRI resulted in a higher tumor volume than in T1w volumetry, whereas the tumor volume in T1w MRI approached the volume in T2w MRI with increasing contrast agent dosage. Histology revealed an apparent tumor volume that corresponded to the volume of the hypointense center in T1w MRI. In contrast, T1 time decrease and T1w signal increase occurred mainly in the tumor rim. - Conclusion - Increasing the contrast agent dosage led to an increase in apparent tumor volume. High-dose T1 MRI, however, overestimated the tumor volume that was determined by histology. Thereby, it can be concluded that standard contrast agent dosage is sufficient to visualize the core tumor volume in T1w MRI. Measurement of tumor volume after increasing contrast agent dosage depicts tumor core and edema, which can be due to diffusion or accumulation or both. Tumor core and edema, however, can be visualized by T2w MRI without need of additional contrast agent.